Plant Study Of Portulaca Grandiflora In Green Roof Application For Rainwater Harvesting - Rosli, Fatin Norliana (Universiti Sains Malaysia, 2021)
A green roof is one of the current technology or approach to counter the negative impacts of urbanization. Instead of that, many researchers believe that the green roof can act as a source of contaminants. To solve this problem, the Portulaca Grandiflora was chosen as potential vegetative components to reduce the contaminants in the green roof system by using phytoremediation techniques. Thus, the greenhouse model with a size of 20cm x 20cm x 45cm was divided into two types which include Control column sample and Plant column sample. The percentages removal of the parameters between Control column and Plant column sample were observed for 4 weeks duration. In this experiment, the average percentage removal of the parameters recorded by the Portulaca Grandiflora was 32.24% (COD), 44.79% (TP), 37.20% (Turbidity), 34.67% (Colour), 39.04% (Iron), and 82.02% (Zinc). On the other hand, the average range of pH value in Portulaca grandiflora sample was from 6.48 to 7.16. In the short period of time experiment, the changes of TKN value by Portulaca Grandiflora could not be observed as the system was not yet stabilize. The after-treatment values for each parameter fell within class IIA/IIB when compared to the NWQS values, which will just require the conventional treatment for water supply usage. Therefore, the Portulaca Grandiflora has a potential to be used as vegetation in the green roof system as its capable of removing the contaminants in the system.